An analysis of factors that influence diners to use restaurant review websites - Brewer, Prawannarat (Archives of Business Research, 2020)
The purpose of this study is to explore why diners use restaurant review websites and how restaurant owners can obtain maximum benefit from these sites. By employing the Stimulus-Organism-Response framework, three key attributes of a restaurant review website were explored to discover their impact on consumers’ attitudes and behavioral responses. These attributes included performance, appearance, and content. A mock restaurant review website was created according to the results of in-depth interviews with participants who frequently used restaurant review websites. In the final study, an online survey was conducted. Data were collected from residents of the Southeastern U.S. and yielded 529 completed responses. The results provided support for the structural model. The three attributes of a restaurant review website had significant influences on consumers’ recommendation adoption and intentions to revisit the site in the future. Research implications, limitations, and suggestions were discussed